REVITALISATION OF MORAL VALUES IN MINANGKABAU CULTURE: PERSPECTIVE MODEL OF REALITY COUNSELING - Darimis Darimis (International Conference on Languages and Arts, 2014)
Minangkabau loaded moral values​​ based on"custom basandi syarak, syarak basandi kitabullah", such as those encountered in the Minangkabau cultural institutions, ideally become a major modality in building individual character. Moral values ​​such as life was sized and futures, a sense of shame and check, polite, considerate, brave as true, wise, perceptive and patient, diligent and humble is an aspect of Minangkabau moral values ​​can be guided to form a human Minangkabau character. Today moral values ​​began to be eroded by foreign culture, such as cultural life materialistic, hedonistic, and sekularistic, so that individuals grow and grew up with a culture that ran from the Minangkabau identity. In this regard, the revitalization of moral values ​​need to be done to reinforce the values ​​that have been weakened through education, such as through the provision of counseling models of reality. Counseling reality as one of the counseling model has a basic principle that human beings have basic needs and strive to fulfill it. The basic needs include the need to survive, to love and be loved, power and achievement, freedom and pleasure. The need to love and be loved becomes a major requirement. Individual success in meeting basic needs will provide success in his identity, while the failure to meet the basic needs of individuals develop identities lead to failure. Keywords: moral values​​, Minangkabau culture, reality counseling